2016
DOI: 10.1111/lam.12669
|View full text |Cite
|
Sign up to set email alerts
|

Trend of extensively drug-resistantAcinetobacter baumanniiand the remaining therapeutic options: a multicenter study in Tehran, Iran over a 3-year period

Abstract: The high frequency of drug-resistant phenotypes including carbapenem-resistant Acinetobacter baumannii, multidrug-resistant, and extensively resistant has been demonstrated in Ac. baumannii isolates tested here. As the antibiotic resistance pattern of isolates varies in different geographical regions, this study can provide comprehensive information about the antibiotic resistance profile of Ac. baumannii isolates in Tehran. In addition, the resistance profiles could be effectively considered by clinicians to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 41 publications
1
9
1
1
Order By: Relevance
“…In the present study, we observed a significant MDR (21.9%) and XDR (18.8%) frequency. The XDR rate in this study was lower than the usual reported rates of clinical A. baumannii isolates, as it reached more than 90% in one report from Tehran (7). However, the MDR rate in this study was higher than reported rates of clinical isolates.…”
Section: Discussioncontrasting
confidence: 85%
See 2 more Smart Citations
“…In the present study, we observed a significant MDR (21.9%) and XDR (18.8%) frequency. The XDR rate in this study was lower than the usual reported rates of clinical A. baumannii isolates, as it reached more than 90% in one report from Tehran (7). However, the MDR rate in this study was higher than reported rates of clinical isolates.…”
Section: Discussioncontrasting
confidence: 85%
“…We screened surfaces and equipment of five hospitals and observed a high frequency (53.1%) of CRAB isolates which were simultaneously resistant to some tested antimicrobial agents. Previously, the high distribution of XDR A. baumannii in clinical isolates was reported in hospitals of Tehran, central Iran (7,17). Based on the present results, tigecycline exhibited promising in vitro activity against A. baumannii isolates.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In 2015, we reported the resistance profiles of 401 clinical A. baumannii isolates recovered from 5 hospitals in Iran between 2011 and 2013, with 90% of the isolates being found to be extensively drug resistant (XDR) (20). Later, all the isolates were further examined using allele-specific PCRs (21), and 57 (14%) and 86 (22%) isolates were found to belong to GC1 and GC2, respectively (22).…”
mentioning
confidence: 99%
“…In addition, a more recent study carried out on 105 A. baumannii isolates showed that all were multidrug resistant and 71.4% were XDR (23). A multi-hospital study performed in Iran over a three-year period from 2011 to 2013 has also shown that 91.3% of A. baumannii isolates were XDR (24).…”
Section: Discussionmentioning
confidence: 99%